Komunikasi Interpersonal Suami dan Istri Dalam Mencegah Perceraian di Ponorogo - Mohammad luthfi (Universitas Darussalam Gontor collaboration with ISKI (Ikatan Sarjana Ilmu Komunikasi Indo, 2017)
This study aims to determine the interpersonal communication of husband and wife in preventing divorce. The location of research in Ponorogo Regency with the subject of research five couples who have been divorced by Ponorogo Religious Court. The method used in this study is descriptive qualitative with data collection techniques through interviews, observation and documentation. The results showed that interpersonal communication husband and wife less well awakened due to disharmony interpersonal relationships in the family. Factors that lead to disharmony interpersonal relationships in the family is the attitude of disbelief between husband and wife caused by lack of honesty and mutual attitude of each partner in the family causing interpersonal conflict and lead to divorce. This study provides recommendations to the community, especially couples to build good interpersonal communication in the family by always putting honest and open attitude so that any problems that arise in the family can be resolved properly.